Allogeneic expanded adipose‐derived stem cells in the treatment of rectovaginal fistulas in Crohn's disease. (4th September 2020) - Nikolic, M.; Stift, A.; Reinisch, W.; Vogelsang, H.; Matic, A.; Müller, C.; von Strauss und Torney, M.; Riss, S.
Abstract: Aim: Crohn's disease (CD)‐related rectovaginal fistulas (RVFs) are rare, challenging to treat and associated with a high morbidity. Due to a significant lack of data, we aimed to analyse the safety and feasibility of allogeneic adipose‐derived stem cells (ASCs) in the treatment of CD‐related RVF. Method: Four consecutive patients with CD‐related RVF underwent treatment with expanded allogeneic ASCs extracted from a healthy donor in a tertiary referral centre in 2019. None of the patients had an intestinal diversion at the time of the treatment. Follow‐up was performed 6 months postoperatively. Results: The median operation time was 45 min with a median hospital stay of 3 days. No intra‐operative complications occurred. Three patients (75%) developed recurrent RVF after a median follow‐up of 19 days. Two patients required surgical treatment including loose seton drainage due to discharge and pain. One patient developed recurrence of symptoms after 10 days, but refused further surgical therapy. Only one patient (25%) showed healing of the RVF, with re‐epithelialization of both the vaginal and rectal opening and absence of clinical symptoms. Conclusion: Expanded allogeneic ASC therapy represents a novel safe treatment option for CD‐associated RVF. Although efficacy appears limited, further controlled studies are required to draw robust conclusions.